Endocrine and regenerative mechanisms of adipose-derived stem cells in female infertility - Merhi, Zaher; Garg, Bhavika; Haroun, Jessica (Frontiers in Endocrinology, 2025)
Infertility remains a global health challenge, particularly in cases involving endometrial damage, diminished ovarian reserve, or poor embryo quality where conventional therapies often fail. Adipose-derived stem cells (ADSCs) have emerged as a promising regenerative option due to their accessibility, multipotency, and paracrine signaling capacity. This review evaluated preclinical and clinical studies investigating ADSCs and their derivatives for uterine, ovarian, and embryo applications in reproductive medicine. Literature searches were conducted in PubMed to July 2025, focusing on studies involving ADSCs, ADSC exosomes, and ADSC mitochondria in animal models and human studies. Results demonstrated that intrauterine ADSC administration improved endometrial thickness, vascularization, and receptivity, with some studies showing increased implantation and pregnancy rates in patients with thin endometrial lining thickness or Asherman’s syndrome. Ovarian applications showed partial restoration of function in premature ovarian insufficiency and chemotherapy-induced damage, with evidence of menstrual recovery, hormonal improvements, and enhanced folliculogenesis in both animal and early human studies. At the gamete and embryo level, ADSC-derived mitochondria, exosomes, and conditioned media improved oocyte maturation, reduced oxidative stress, enhanced blastocyst development, and increased embryo survival in vitro. Collectively, these findings highlight ADSCs’ therapeutic potential in addressing multiple infertility etiologies. However, current evidence is limited by small sample sizes, heterogeneous methodologies, short follow-up periods, and incomplete mechanistic insight. Most evidence to date comes from animal studies, while human clinical data remain limited to small early-phase trials. Large, well-designed clinical studies with standardized protocols and long-term safety evaluation are essential before ADSC-based therapies can be responsibly considered for full integration into assisted reproductive technologies.